EU recovery plans, inclusive knowledge economy and overcoming regional disparities - Nahtigal, Matjaž (Lex localis, 2022)
The EU has adopted the Recovery and Resilience Facility (RRF) as the key instrument help to ensure that the EU, its member states, regions and local communities emerge stronger and more resilient from the pandemic crisis. Its main goal is to achieve climate neutrality by 2050, and it sets Europe on a path of digital transition, creating jobs and spurring growth in the process. The EU recovery plans should be seen as an opportunity not merely to address the post-pandemic health, social, economic and financial crisis – further exacerbated by the ongoing war in Ukraine – but primarily to develop a more inclusive and innovative institutional framework for European economies with more resilient local communities, small and medium sized firms, and high-quality public services across the EU. New forms of participation, more policy space, tools and instruments to support local and regional development strategies are necessary to establish an overall environment more hospitable to sustainable and inclusive development. Diversity of European local communities and European regions at different levels of development require tailored-made approach to realize their development potential. Institutional innovations, such as the regional public venture funds, may be the key to overcome regional disparities and build regional knowledge economies. The positive experience with the recovery, sustainable transition and inclusive knowledge economy across the European Union may serve as an important experience and encouragement to many other parts of the world, coping with the post-pandemic recovery, implementation of the Sustainable Development Goals and inclusive development.
Keywords: Covid-19; družbene razmere; Ekonomska politika; Evropska unija; gospodarski razvoj; lokalne skupnosti; Pandemije; razvojna strategija; regije; trajnostni razvoj